Multiple Lactations: Effect of Successive Lactation on Milk Production and Infant Milk Intake - Ashleigh H. Warden; Vanessa S. Sakalidis; Jacki L. McEachran; Ching Tat Lai; Sharon L. Perrella; Donna T. Geddes; Zoya Gridneva (Proceedings)
Optimal infant growth is reliant on both the production and intake of sufficient human milk. Some studies, in particular animal models, suggest that multiparous mothers produce a higher yield of milk compared to primiparous mothers. The aim of this study was to examine whether there is a relationship between successive lactations and maternal 24 h milk production and infant milk intake. Lactating mothers who did not feed commercial milk formula (n = 22) measured their milk production at 1–6 months postpartum by test-weighing their infants for 24 h during two consecutive lactations (L1: at 3.0 ± 1.2 months, L2: at 2.6 ± 1.0 months; (p = 0.26)) and provided the dyad’s demographics. Twenty-four-hour milk production by breast, infant 24 h milk intake (including mothers’ own expressed milk), and breastfeeding and expressing frequencies were measured. Statistical analysis used linear mixed modelling accounting for infant birth weight and the random effect of participant. There were no differences between L1 and L2 for milk production (L1: 748 ± 122 g; L2: 768 ± 157 g; p = 0.57), infant milk intake (L1: 744 ± 133 g; L2: 776 ± 189 g; p = 0.50), 24 h breastfeeding frequency (L1: 13 ± 4; L2: 12 ± 3; p = 0.28), and expression frequency (L1: 1.4 ± 1.9; L2: 1.4 ± 2.8; p = 0.95). Birth weight was higher with the successive lactation (L1: 3260 ± 345 g; L2: 3509 ± 237 g; p = 0.002). Infant sex was not associated with 24 h milk production (p = 0.21), milk intake (p = 0.62), or breastfeeding frequency (p = 0.17). The findings of this study suggest that in humans there is no effect of successive lactations or infant sex on 24 h milk production or infant milk intake.